PEMANFAATAN TEKNOLOGI LMS DENGAN PENDEKATAN TPACK DI SDN LARANGAN 9 KOTA TANGERANG - Yulhendri Yulhendri; Ratnawati Susanto; Diah Aryani (Jurnal Abdimas Bina Bangsa, 2023)
This Abdimas aims to provide training and coaching to the teachers of SDN Larangan 9 Kota Tangerang in the application of Learning Management System (LMS) technology with the Technological Pedagogical and Content Knowledge (TPACK) approach to improve the quality of learning in the digital era. This activity uses the community service method with stages of activities including identifying needs and challenges, training and fostering the use of LMS, as well as evaluating and monitoring implementation results. The results of the training and coaching show that teachers at SD Larangan 9 Tangerang City are able to apply LMS technology with the TPACK approach in learning more effectively and efficiently. In this case, teachers are able to integrate knowledge of technology, education, and learning materials in a more integrated manner, so that learning can become more interactive, creative, and interesting for students. Therefore, the application of LMS technology with the TPACK approach can improve the quality of learning in the digital era and support the creation of a more competent generation in the future